Laparoscopic cornual resection for interstitial pregnancy - a case report: Laparoskopska resekcija roga maternice pri intersticijski nosečnosti - klinični primer - Bizjak, Tina; Rakić, Saša (Acta Medico-Biotechnica, 2021)
Purpose: Ectopic pregnancy is defined as the implantation of a fertilized egg outside of the uterine endometrium. Previous research has reported an increase in the incidence of ectopic pregnancy and estimated that this condition occurs in 1.5 to 2.5% of pregnancies (1). In cases of ectopic pregnancy, the fertilized egg most often implants in the fallopian tubes. In some cases, it can also implant at the site where the fallopian tube and the uterus join; this is a condition referred to as interstitial pregnancy (2). Rupture of interstitial pregnancy can have catastrophic consequences with a mortality rate of up to 2% (2, 3).Case report: Here, we report the case of a 33-years-old patient with an interstitial pregnancy in the right uterine horn. We successfully performed laparoscopic surgery with a harmonic scalpel and preliminary coagulation of the uterine artery without any complications. Following surgery, the pregnancy was normal and was carried to term.Conclusions: Previously, the treatment of interstitial pregnancy was mostly performed surgically by open surgery including resection of the affected horn of the uterus (4). However, several successful clinical cases of laparoscopic surgery have now been reported (5-8). In our opinion, laparoscopic resection, with a harmonic scalpel and preliminary coagulation of the uterine artery, represents a safe and efficient techniqueand should be used more regularly in the treatment of interstitial pregnancy.
Keywords: interstitial pregnancy; laparoscopic surgery; harmonic scalpel